Music, Time and Being – The Constitution of the Heideggerian Mousiké - Costa Silva, Jose Eduardo; Monte, Gilmar Antonio (Cultural Arts Research and Development, 2025)
This article offers a philosophical reflection on the concept of music within the framework of Martin Heidegger’s thought. It argues that music can be understood as an immediate articulation of time, drawing upon Heidegger’s major works: The Concept of Time, Being and Time, Time and Being, Nietzsche, The Origin of the Work of Art, and On the Way to Language. Through these readings, the article develops the hypothesis that music expresses the category of time insofar as time essentially constitutes its structure. The aim is to investigate how music, from a Heideggerian perspective, transcends its merely aesthetic or expressive dimensions and takes on an ontological significance.In this context, music is interpreted as mousiké, the original Greek conception that integrates sound, rhythm, word, and gesture as a unified act of sense-making. Music, thus, is approached as lógos—the revealing word that grants meaning to being through language. The argument unfolds in three sections: first, an analysis of the concept of time in Heidegger’s philosophy; second, an exploration of time as a structural component of beings; and third, a discussion of music’s essential connection with time and its relation to the Heideggerian notion of mousiké. The article concludes that music, within Heidegger’s ontology, serves as a primordial manifestation of temporality and participates in the revelation of being through language and silence.